The Three-Layered DNA Uptake Machinery at the Cell Pole in Competent Bacillus subtilis Cells Is a Stable Complex - Kaufenstein, Miriam (American Society for Microbiology (ASM), 2011)
Many bacteria possess the ability to actively take up DNA from the environment and incorporate it into the chromosome. RecA protein is the key protein achieving homologous recombination. Several of the proteins involved in the transport of DNA across the cell envelope assemble at a single or both cell poles in competent Bacillus subtilis cells. We show that the presumed structure that transports DNA across the cell wall, the pseudopilus, also assembles at a single or both cell poles, while the membrane receptor, ComEA, forms a mobile layer throughout the cell membrane. All other known Com proteins, including the membrane permease, localize again to the cell pole, revealing that the uptake machinery has three distinct layers. In cells having two uptake machineries, one complex is occasionally mobile, with pairs of proteins moving together, suggesting that a complete complex may lose anchoring and become mobile. Overall, the cell pole provides stable anchoring. Only one of two uptake machineries assembles RecA protein, suggesting that only one is competent for DNA transfer. FRAP (fluorescence recovery after photobleaching) analyses show that in contrast to known multiprotein complexes, the DNA uptake machinery forms a highly stable complex, showing little or no exchange with unbound molecules. When cells are converted into round spheroplasts, the structure persists, revealing that the assembly is highly stable and does not require the cell pole for its maintenance. High stability may be important to fulfill the mechanical function in pulling DNA across two cell layers.